Endophytic fungi from calamus kerrianus and Wallichia caryotoides (Arecaceae) at Doi Suthep-Pui National Park, Thailand - Saisamorn Lumyong (2018)
Fungal endophytes associated with the palms, Calamus kerrianus (rattan) and Wallichia caryotoides (taorang) were investigated at two sites within Doi Suthep-Pui National Park, Thailand. Endophytic fungi were isolated from different tissue types (petiole, leaf, lamina and leaf veins) during three periods of the year, rainy season (July-October, 1999), cold season (November 1999-February 2000) and hot season (March-June 2000). Thirty-five endophytic fungi isolated included xylariaceous taxa (20 morphotypes), sterile mycelia, one unidentified and 13 mitosporic fungi including Cladosporium sp., Colletotrichum gloeosporioides, Corynespora-like sp., Fusarium sp., Guignardia cocaicola, Paecilomyces sp. Pestalotiopsis sp., Phialophora sp., Phoma sp., Phoma-like sp., Phomopsis sp., Phyllosticta sp., and Sarcopodium sp. The endophyte species, their relative frequency, isolate prevalence and diversity did not differ significantly between host species, tissue types, study sites and seasons.